TECHNOLOGICAL INNOVATIONS IN STORAGE AND PROCESSINGAGRICULTURAL PRODUCTS - LIPNITSKIY, Roman; KHOLODIUK, Oleksandr (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The world we live in is constantly changing, and these changes affect all aspects of our lives, including agriculture. Population increase, climate change, urbanization and increased consumer demands for food quality and safety create new challenges for agriculture. That is why technological innovations in the field of storage and processing of agricultural products are becoming particularly relevant. The article discusses in detail the role of digital technologies in the transformation of the agro-industrial sector. Special attention is paid to the analysis of such innovative solutions as precision agriculture, automation of production processes, use of artificial intelligence and machine learning systems. These technologies make it possible to optimize resources, reduce the impact of the human factor, increase productivity and ensure high quality, significant emphasis is placed on the implementation of modern methods of monitoring justified climatic conditions, the use of drones, sensors and specialized software solutions for plant protection and yield forecasting. It is shown how these approaches contribute to a more rational use of water and land resources, as well as minimizing the negative impact on the environment. The article also contains an analysis of the main challenges that arise during the implementation of digital solutions in the agricultural sector. Among them are high initial investments, necessary improvement of digital literacy of farmers and adaptation of legislative norms. At the same time, the prospects of digitalization are highlighted, in particular, its role in ensuring global food security, reducing product losses at all stages of production, and achieving the goals of sustainable development. Thus, the work emphasizes the need to integrate innovative approaches in agriculture as a key condition for solving modern problems and ensuring the long-term development of the industry.